Association between socioeconomic position and the prevalence of type 2 diabetes in Ghanaians in different geographic locations: the RODAM study. Issue 7 (27th March 2017) - Addo, Juliet; Agyemang, Charles; de-Graft Aikins, Ama; Beune, Erik; Schulze, Matthias B; Danquah, Ina; Galbete, Cecilia; Nicolaou, Mary; Meeks, Karlijn; Klipstein-Grobusch, Kerstin; Bahendaka, Silver; Mockenhaupt, Frank P; et al.
Abstract : Background: The prevalence of diabetes has been shown to be socially patterned but the direction of the association in low-income countries and among migrant populations in Europe has varied in the literature. This study examined the association between socioeconomic position (SEP) and diabetes in Ghanaians in Europe and in Ghana. Methods: Data were derived from the multicentre Research on Obesity and Diabetes among African Migrants (RODAM) study of Ghanaian adults aged 25–70 years residing in Europe (Amsterdam, Berlin and London) and in urban and rural Ghana. Educational attainment (elementary, secondary or higher) and occupational class (low or high) were used as indicators of SEP. Age-standardised prevalence of diabetes and prevalence ratios were evaluated separately for men and women of different SEP in Ghana and Europe. Results: A total of 5290 participants were included in the analyses. The prevalence of diabetes decreased with increasing level of education in Ghanaian men and women in Europe and in men in urban Ghana, whereas diabetes prevalence increased with increasing level of education in men and women in rural Ghana. The association between occupational class and the prevalence of diabetes followed a less consistent pattern in men and women in the different locations. Conclusions: The association of diabetes and SEP differed in rural Ghana compared with urban settings in Ghana and Europe and comparing men and women, highlighting the complex interaction of SEP and the development of diabetes. These findings have important implications for diabetes prevention strategies in Ghanaians in different locations.